Transcriptomic and Metabolomic Characterization of Volatile Flavor Compound Dynamics in Dragon Fruit (Selenicereus spp.) Development - Zhi-Jiang Wu; Ri-Wen Ji; Ze-Jian Huang; Xiao-Ying Ye; Li-Fang Huang; Hai-Yan Deng; Gui-Feng Lu; Shuo-Tong Wei; Chao-An Liu; Zhen-Ying Li; Hong-Li Li; Gui-Dong Liang (Horticulturae, 2025)
Dragon fruit comprises a wide variety of species that are rich in nutritional value and have great economic potential; however, numerous studies have focused on their nutritional and commercial quality. In contrast, few studies have addressed their flavor quality, particularly with respect to the regulatory networks responsible for their flavor-related substance contents. To this end, we sequenced the transcriptomes and metabolomes of red-skin/white-fleshed and red-skin/red-fleshed dragon fruit at different timepoints during fruit development. RNA-seq and metabolome data were used to divide the seven developmental stages of the dragon fruit into four categories (young fruit, expansion, maturity, and senescence). In all, 16,827 differentially expressed genes (DEGs), including 958 transcription factors, were identified and grouped into 10 clusters, and the pathways in each cluster were annotated. Additionally, 318 differentially accumulated metabolites (DAMs) were identified, including 88 common metabolites. The main flavor-related substances and the key genes regulating them were determined via joint analysis via RNA-seq and metabolomics. Furthermore, 10 volatile active components related to green flavors and aromas were screened according to the relative odor activity value (ROAV), and 15 candidate genes related to key flavor compounds were screened via WGCNA, 3 of which encoded transcription factors. In conclusion, our results provide a theoretical basis for an in-depth understanding of the volatile flavor compounds in dragon fruit and provide new genetic resources for the subsequent study of fruit flavor compounds.